2016
DOI: 10.1002/jcp.25426
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic Acid Inhibits Invasion and Migration and TGF‐β‐Induced EMT of Lung Cancer Cells Through PI3K/Akt/mTOR Inactivation

Abstract: Epithelial-to-mesenchymal transition (EMT) is a critical cellular phenomenon regulating tumor metastases. In the present study, we investigated whether ginkgolic acid can affect EMT in lung cancer cells and the related underlying mechanism(s) of its actions. We found that ginkgolic acid C15:1 (GA C15:1) inhibited cell proliferation, invasion, and migration in both A549 and H1299 lung cancer cells. GA C15:1 also suppressed the expression of EMT related genes (Fibronectin, Vimentin, N-cadherin, MMP-9, MMP-2, Twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
155
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 59 publications
9
155
0
1
Order By: Relevance
“…Previous studies have shown that GA exhibit promising antitumor activities. The wound-healing and anti-migratory effects on pancreatic and lung cancer have been previously described [12, 14]. We found that GA have anti-migratory effects on the triple-negative MDA-MB-231 breast cancer cell line as well as in the less invasive MCF-7 cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Previous studies have shown that GA exhibit promising antitumor activities. The wound-healing and anti-migratory effects on pancreatic and lung cancer have been previously described [12, 14]. We found that GA have anti-migratory effects on the triple-negative MDA-MB-231 breast cancer cell line as well as in the less invasive MCF-7 cells.…”
Section: Discussionsupporting
confidence: 66%
“…The viability of pancreatic cancer cells was suppressed by GA. In addition, GA induced apoptosis and impaired migration, invasion and the colony-forming capability of cancer cells [1214]. GA also inhibited de novo lipogenesis in cancer cells by activation of AMP-activated protein kinase (AMPK) signaling and downregulation of several key enzymes involved in this process [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent work suggested that GA inactivates PI3K/Akt/mTOR in lung cancer cells (Baek et al, 2016). The PI3K/Akt/mTOR is a crucial pathway regulating autophagy and synaptic plasticity in the brain (Heras-Sandoval et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we chose the classic EMT markers E-cadherin, β-catenin, vimentin and Snail for evaluation of the effect of ORI on EMT. TGF-β1 is the most well characterized factor responsible for induction of EMT (53,54). In our preliminary experiment, without the addition of TGF-β1, the EMT marker not changed obviously in A375 and B16-F10 cells, so we can not well evaluated the ORI's effect on EMT (data not shown).…”
Section: Discussionmentioning
confidence: 79%